Kajian Perkawinan Campuran dalam Perspektif Hukum Perdata Internasional (Perkawinan antara Warga Indonesia dan Warga Belanda) - Renti Friska Pangaribuan; Winda Fitri (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The rapid progress of science and innovation affects the simplicity of relations between individuals and nations. One of the impacts is the mixing of relations between couples with different identities, including Indonesian experts and workers from various countries. Issues that mixed-identity relationship strategy are the stage of producing supporting documents from the marriage registrar and at the different stages of planning archives. The purpose of this legal research is to identify and analyse mixed marriages between Indonesia and Netherlands also the procedures under international civil law. The method using normative juridicial research based on statute approach and conceptual approach.